The global and national burden of chronic kidney disease attributable to ambient fine particulate matter air pollution: a modelling study - Yan Yan; Benjamin Bowe; Yan Xie; Ziyad Al-Aly; Elena Artimovich; Miao Cai (BMJ Global Health)
Introduction We aimed to integrate all available epidemiological evidence to characterise an exposure–response model of ambient fine particulate matter (PM2.5) and the risk of chronic kidney disease (CKD) across the spectrum of PM2.5 concentrations experienced by humans. We then estimated the global and national burden of CKD attributable to PM2.5.Methods We collected data from prior studies on the association of PM2.5 with CKD and used an integrative meta-regression approach to build non-linear exposure–response models of the risk of CKD associated with PM2.5 exposure. We then estimated the 2017 global and national incidence, prevalence, disability-adjusted life-years (DALYs) and deaths due to CKD attributable to PM2.5 in 194 countries and territories. Burden estimates were generated by linkage of risk estimates to Global Burden of Disease study datasets.Results The exposure–response function exhibited evidence of an increase in risk with increasing PM2.5 concentrations, where the rate of risk increase gradually attenuated at higher PM2.5 concentrations. Globally, in 2017, there were 3 284 358.2 (95% UI 2 800 710.5 to 3 747 046.1) incident and 122 409 460.2 (108 142 312.2 to 136 424 137.9) prevalent cases of CKD attributable to PM2.5, and 6 593 134.6 (5 705 180.4 to 7 479 818.4) DALYs and 211 019.2 (184 292.5 to 236 520.4) deaths due to CKD attributable to PM2.5. The burden was disproportionately borne by low income and lower middle income countries and exhibited substantial geographic variability, even among countries with similar levels of sociodemographic development. Globally, 72.8% of prevalent cases of CKD attributable to PM2.5 and 74.2% of DALYs due to CKD attributable to PM2.5 were due to concentrations above 10 µg/m3, the WHO air quality guidelines.Conclusion The global burden of CKD attributable to PM2.5 is substantial, varies by geography and is disproportionally borne by disadvantaged countries. Most of the burden is associated with PM2.5 levels above the WHO guidelines, suggesting that achieving those targets may yield reduction in CKD burden.